Impact of NOx emissions on air quality simulations with the Bulgarian WRF-CMAQ modelling system. (2015) - Syrakov, Dimiter; Prodanova, Maria; Georgieva, Emilia; Etropolska, Iglika; Slavov, Kiril
The WRF-CMAQ modelling system was applied for air quality simulation over Europe in the frame of the air quality model evaluation international initiative (AQMEII), phase 2. The models were run for the year 2010 for a domain of 5, 000 × 5, 000 km² with a horizontal grid resolution of 25 km. A preliminary evaluation of model results vs. EU surface measurements was conducted using JRC web-based ENSEMBLE platform. Model performance was characterised by overestimation for ozone and underestimation for NO2 . Trying to understand this fact, another set of NOx emissions, a more complete one, was prepared and the simulations were repeated for the entire year (BG1 and BG2 sets). The increase of NOx emissions with 30% slightly increase the quality of the simulation - the overestimation of O3 decreases by a few percent and NO2 concentrations increase and reach observed levels at rural sites, while they still remain underpredicted at urban sites.